Prinsip dan Strategi Ukuran Investasi - Ar Royyan Ramly (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2017)
Placement of property (maal) on business activities or objects that can be developed by expecting return and facing a state of loss or risk is referred to as an investment. The Islamic concept of investment not only leads people to invest in eternal destinies such as alms, zakat, waqf, grants, and infaq. But in practice many investment instruments that can be developed from sharia products such as sukuk, sharia mutual funds, and Islamic stock. In addition to investing in an investor must understand the form of investments that are run, the type of investment, investment strategy used both through selected instruments and products used. Thus this paper discusses the current investment principles in today’s growing world and the size and investment strategy chosen by investors, which determinesthe cause of the investor’s profit and risk-taking.